Brain damage in fatal non-missile head injury without high intracranial pressure. Issue 1 (January 1988) - Graham, D I; Lawrence, A E; Adams, J H; Doyle, D; McLellan, D R
Abstract : As part of a comprehensive study of brain damage in 635 fatal non-missile head injuries, the type and prevalence of brain damage occurring in the absence of high intracranial pressure were analysed. Of 71 such cases, 53 sustained their injury as a result of a road traffic accident; only 25 experienced a lucid interval. Thirty eight had a fractured skull, a mean total contusion index of 12.9 and diffuse axonal injury in 29: severe to moderate ischaemic damage was present in the cerebral cortex in 25, brain swelling in 13, and acute bacterial meningitis in nine. The prevalence and range of brain damage that may occur in the absence of high intracranial pressure are important to forensic pathologists in the medicolegal interpretation of cases of fatal head injury.